2013
DOI: 10.1371/journal.pone.0068944
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Characteristics and Social Networks of Suicidal Prisoners: Towards a Model of Suicidal Behaviour in Detention

Abstract: Prisoners are at increased risk of suicide. Investigation of both individual and environmental risk factors may assist in developing suicide prevention policies for prisoners and other high-risk populations. We conducted a matched case-control interview study with 60 male prisoners who had made near-lethal suicide attempts in prison (cases) and 60 male prisoners who had not (controls). We compared levels of depression, hopelessness, self-esteem, impulsivity, aggression, hostility, childhood abuse, life events … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
111
3
11

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(136 citation statements)
references
References 52 publications
(67 reference statements)
11
111
3
11
Order By: Relevance
“…This finding is in accord with previous literature sampling populations across countries, communities, and psychiatric settings [3,8,23,26,37]. Two further studies, found that low levels of self-esteem were associated with suicidality in male [41], and female prisoners [50]. In the current study, the relationship between low self-esteem and suicidality was driven by the hopelessness component of the suicidality measure, but not the hostility, suicidal ideation, or negative evaluation components.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This finding is in accord with previous literature sampling populations across countries, communities, and psychiatric settings [3,8,23,26,37]. Two further studies, found that low levels of self-esteem were associated with suicidality in male [41], and female prisoners [50]. In the current study, the relationship between low self-esteem and suicidality was driven by the hopelessness component of the suicidality measure, but not the hostility, suicidal ideation, or negative evaluation components.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, aspects of the prison environment may intensify suicidality. For example, being incarcerated can lead to fear, a lack of agency, a lack of trust [29], and social isolation [41]. Occupying a single cell has been associated with suicide deaths in prisoners [16].…”
Section: Introductionmentioning
confidence: 99%
“…Overall, these findings do not support control theory expectations: Detainees with weak peer bonds were not at increased risk of peer aggression. Our study thus adds to a small body of literature that finds social integration within correctional settings may not operate in the same way it does in the general population, and may actually contribute to adverse mental health outcomes (Lindquist, 2000; Rivlin, Hawton, Marzano, & Fazel, 2013). …”
Section: Discussionmentioning
confidence: 78%
“…Social networks have been used in the past few years to study the relationship between social contagion and a range of outcomes such as obesity, smoking, and happiness [38]. Although isolating causal mechanisms in these types of observational studies is challenging [39], it has been demonstrated that some of the results on social contagion are robust to certain types of confounding [40]. Social networks can also improve understanding of mental illness in controlled prospective settings such as the likelihood of suicide in prisoners [39].…”
Section: Data Variety: Focus On Passive Datamentioning
confidence: 99%